ERP implementation in an IT organization: a case study Laboratory information management system (LIMS) - Suominen, Juho (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
This is a case study on a laboratory information management system (LIMS) project. The study examines the success of the system, its development, and its implementation in a certification laboratory, along its contributing factors. The system in question was developed from scratch within the investigated organization to simplify work and manage growing data streams. Microsoft Office tools had proved to be insufficient in solving the issues that faced the laboratory. The author of this study was a member of the development team and thus in an advantageous position for research. Unfortunately, the development project was terminated due to restructuring of the organization soon after the system had been implemented. The research question of this study was on the success of the LIMS system. This question was answered by examining this software artifact by utilizing eight common evaluation criteria for information systems. These were: functionality, completeness, consistency, accuracy, performance, reliability, usability, and fit with the organization. Similarly, the development project itself was also examined through twelve most common critical success factors (CSF) that were identified from relevant literature. The evaluation was done through both participatory research as a member of the development team and semi-structured interviews with other involved members of the organization. Finally, the results of this case study were reflected against prevailing enterprise resource planning system and CSF theory. The developed LIMS can be considered a success based on the evaluation criteria, as all of them reached at least a satisfactory level. Furthermore, this was also supported by the opinions voiced during the interviews. However, out of the twelve selected CSFs, three failed and five produced mixed results. This leaves only four successful CSFs, which is a significant finding, as these represent the twelve most commonly cited CSFs in relevant literature. Despite these numerous failed CSFs, the project itself was a success, producing a successful software artifact. As a conclusion, it can be said that some of the assumed most important CSFs did not amount to in fact critical factors of success in the scope of this study. Instead, successes with: top management support, ERP team composition and skills, the project champion, and system analysis, selection and technical implementation, were sufficient in this case, possibly making up for the partially or completely failed CSFs. However, reasons for this are outside the scope of this study.